POSSIBLE FUTURE DEVELOPMENT DIRECTION OF AMUSEMENT PARKS IN LATVIA - Rivza, Baiba; Plūmīte, Uldis (Journal of Regional Economic and Social Development, 2021)
Amusement parks have grown rapidly in Latvia over the last 20 years. The development of Latvian amusement parks is determined by several factors related to the economic, political, geopolitical and international market situation. According to the CSB data, the country has a population of 1.9 million and a total of 14 amusement parks or companies providing attractions and entertainment. Part of the problem that the authors emphasize in the paper is that in Latvia, data on amusement parks are not collected separately, but are included in overall data on the tourism industry. This topic has been little studied in all Baltic countries. The topicality of the research relates to the future directions of sustainable development of Latvian amusement parks, which would add value to the growth of this industry. The aim of the research study is to determine the possible directions of development of amusement parks and their main influencing aspects, which determine the future development of these aspects.